Evaluation of Addition of Plant Fixed Oil Extracts (Ginger , Maramia, Eucalyptus) on Some Properties of Heat Cured Denture Base Material - Luma M. Al-Nema; Reem N. Al-Irhayim; Hala Khuder (University of Mosul, College of Dentistry, 2014)
The aim of this study was to evaluate the effect of three types of natural medicinal plants oils on the transverse strength, residual monomer and hardness of polymethylmethacrylate. Materials and methods: Total number of samples of (105) have been prepared in this study. Fifteen samples of heat cured ProBase acrylic resin were prepared without additives ( Control), and (90) samples were pre-pared with additives ( Ginger oil ,Meramia and Eucalyptus oil) in two concentrations (1.5 and 2.5) to evaluate transverse strength, indentation hardness and residual monomer. Results: The results showed a significant difference between control and addition groups in the transverse strength and hardness tests. The addition of oils decreased the transverse strength ,and increased the hardness.There was no significant difference between the residual monomer for control and addition groups, but the control group at the first day showed higher residual monomer release. Conclusion: The addition of eucalyptus , meramia and ginger oils to acrylic resin decreased the transverse strength , increased its hardness and showed no significant difference in residual monomer.